Penerapan Model Pembelajaran Discovery Learning untuk Meningkatkan Hasil Belajar Materi Operasi Bentuk Aljabar pada Siswa Kelas X Akuntansi-2 SMK Negeri I Waingapu - Letu Paulus (Prima Magistra: Jurnal Ilmiah Kependidikan, 2020)
The purpose of this research is to: (1) Improve the learning outcomes of algebraic operation material in grade X students Accounting-2 SMK Negeri I Waingapu in 2018/2019 by implementing the Discovery learning model. (2) To increase the activity of learning Mathematics of algebraic operations in grade X students in Accounting-2 SMK Negeri I Waingapu by implementing the Discovery learning model. This research is a collaborative classroom action (CAR) study implemented in two cycles . The subject in this study was the grade X student Accounting-2 SMK Negeri I Waingapu in 2018/2019 with a total of 36 people. Each cycle consists of two meetings. The data collection techniques used in this study were observations, tests and documentation. The instruments used are observation sheets and tests. Analysis of the data used is the analysis of the implementation of learning, learning outcomes and success criteria. The defined success indicator is when the average class increases from the preset, cycle I and cycle II. The results showed that students’ mathematical learning results were improved. This is evidenced by the increased percentage of the classical, which is from the preview 31%, Cycle I 69% and cycle II 94%. In addition to the observation data obtained before the action, students look less active in learning activities, learning activities are more dominated by teachers. After being given an action, students appear active during a learning activity and at the time of the group discussion